A credible, automated e-voting system in the context of Bangladesh - Sharif, Fairouz; Al Faiyaz, Abdulla (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.